Patrice Motsepe : an appetite for disruption - Smith, Janet, 1967-; Motsepe, Patrice (Johannesburg : Jonathan Ball Publishers, 2022)
Business tycoon Patrice Motsepe is never shy to shake up the status quo. He has always followed his instincts to stay ahead of the curve. An icon of corporate South Africa, he is as much known for his leadership in the world of football as for his philanthropy. He was a top lawyer when he followed his dream of being an entrepreneur, making a deal with Anglo American in the late 1990s that marked the beginning of a series of unique relationships which today define his African Rainbow Minerals empire. As the owner of Mamelodi Sundowns, he led it to becoming one of the most accomplished clubs in Africa. Then came the powerful seats of president at the Confederation of African Football and vice-president of FIFA, football's global governing body, in 2021. Yet questions linger about his political ambitions because of his close links to the ANC and particularly his brothers-in-law, Cyril Ramaphosa and Jeff Radebe. In this unauthorised biography, best-selling author and journalist Janet Smith mines public archives, academic papers and international media to find what lies behind this hugely successful, intensely private man, and what may lie ahead.y--Publisher's description.
Part I. The beloved game -- Part II. Ties that bind -- Part III. Boardrooms and chambers -- Part IV. Coming to the party.
"An unauthorised biography."
Includes bibliographical references (pages 226-244) and index.
Keywords: Motsepe, Patrice, -- 1962-; Businessmen -- South Africa -- Biography